Protective applications of vacuum-deposited perfluoropolymer films - Grytsenko, K.P.; Kolomzarov, Yu.V.; Belyaev, O.E.; Schrader, S. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2016)
The paper summarizes in brief applications of perfluoropolymer thin films deposited from the gas phase by several different methods, for protection of various materials and devices both at the research stage and already in industry. Perfluoropolymer films protect from corrosion coated metals, attain superhydrophobic properties to various surfaces, enhance the lifetime of medical implants, passivating the surface of semiconductors, protect functional layers in organic light emitting diodes, field effect transistors etc. Organic molecules in the PTFE matrix revealed extreme stability and presents the new material for optical applications.